Mindfulness for Anxiety Management and Happiness: The Role of VR, Metacognition, and Hormones - Mitsea, Eleni; Drigas, Athanasios; Skianis, Charalampos (Technium BioChemMed, 2022)
Chronic stress, even at a young age, has become a major health concern with the harmful effects on cognition, mood, and well-being largely underestimated. Mindfulness interventions are well-recognized as effective strategies in stress management. However, we know less about the impact of mindfulness on physiological indicators such as hormones/neurotransmitters. This review study aims to provide representative studies regarding the impact of mindfulness practices on hormones and neurotransmitters, which are responsible for stress regulation, positivity, and wellness. Taking into consideration the difficulties that many people have to follow a conventional mindfulness program, we also investigated the effectiveness of virtual reality as an assistive tool for mindfulness training. The results confirmed our initial hypothesis, according to which mindfulness training reduces stress hormones while increasing hormones/neurotransmitters which induce relaxation along with positivity and self-satisfaction. Virtual reality provides several advantages facilitating training conditions, optimizing the experience, and increasing the effectiveness of interventions. In addition, it strengthens self-control skills. These results indicate also that those physiological parameters, which are considered to be out of human control, can be modified with self-control practices. We conclude that mindfulness practices constitute a form of metacognitive training by which individuals can take control and balance the physiological processes that determine cognition, mood, and well-being. Virtual reality maximizes therapeutic outcomes, especially for people with disabilities or difficulties with conventional interventions.